Moderating Impact of Inflation Rate on the Relationship Between Capital Structure and Financial Performance of Nigerian Consumer Goods Companies - Ibrahim Titus; Daniel Orsaa Gbegi; Umale Okoh (International Journal of Sustainable Applied Sciences, 2023)
The study looked at the relationship between listed consumer companies in Nigeria's capital structure and financial performance, as well as the moderating effect of inflation. While debt to equity was utilised as a capital structure variable, return on asset (ROA) was used as a gauge of financial success. The 13 sampled organisations' audited annual reports covering the 10-year period from 2013 to 2022 were where the study's data came from. Robust fixed effect regression was used in the study as a method of analysis and hypothesis testing. The outcome demonstrates that inflation has a negative moderating effect on capital structure and ROA as well as a negative and significant negative impact on return on assets. According to the study's findings, high leverage businesses in Nigeria's consumer goods industry will struggle financially.  The negative impact of debt in the capital structure on the financial performance of listed consumer goods firms in Nigeria is also exacerbated by inflation. According to the report, management of publicly traded consumer goods companies should evaluate their capital structure in light of rising inflation and develop a comprehensive financial strategy that takes their long-term goals and objectives into account.  This could entail managing debt levels, optimising capital structure, and giving investments with long-term returns first priority.